2015
DOI: 10.1007/s11266-015-9548-4
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Motives for Episodic Volunteering

Abstract: Although episodic volunteers are a critical resource for many organisations, their motives for volunteering are poorly understood. A systematic review was conducted to describe empirical evidence about motives for episodic volunteering (EV) across sectors (sport, tourism, events, health and social welfare). Identified EV motives were then categorised using core functions from the Volunteer Functions Inventory (VFI) for comparison across studies. Twelve databases (1990–December 2014) were searched. Thirty-three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
69
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(77 citation statements)
references
References 39 publications
4
69
0
4
Order By: Relevance
“…Research has long shown much variation in the length of time that a person commits to engaging in volunteering and citizen science activities relating to a number of internal and external factors including intrinsic motivation, time availability, and type of volunteer project (Macduff 2005;Nov et al 2011;Dunn et al 2016). Understanding volunteers' longevity behaviours is important for overall project management in relation to the sustainability and continuity of their practices, adequacy of recruitment and retention, and the allocation of resources (e.g., equipment and training) (Nov et al 2011;Chu et al 2012).…”
Section: Characteristics Of Engagement In Volunteer and Citizen Scienmentioning
confidence: 99%
“…Research has long shown much variation in the length of time that a person commits to engaging in volunteering and citizen science activities relating to a number of internal and external factors including intrinsic motivation, time availability, and type of volunteer project (Macduff 2005;Nov et al 2011;Dunn et al 2016). Understanding volunteers' longevity behaviours is important for overall project management in relation to the sustainability and continuity of their practices, adequacy of recruitment and retention, and the allocation of resources (e.g., equipment and training) (Nov et al 2011;Chu et al 2012).…”
Section: Characteristics Of Engagement In Volunteer and Citizen Scienmentioning
confidence: 99%
“…Given the largely atheoretical nature of episodic and CSE volunteering research (Dunn et al , ; Hyde et al , ), this study draws from two theoretical frameworks validated in volunteering research outside of the CSE context, which may be of relevance to address the gaps identified. First, the volunteer process model (Snyder & Omoto, ) proposes key volunteering constructs and links these constructs in three sequential phases: antecedents to volunteering (e.g.…”
Section: The Current Studymentioning
confidence: 99%
“…satisfaction, connection to the CSE host) and the factors that may contribute to this; and (ii) the need to consider constructs, in addition to motives, that predict CSE volunteer retention and behaviours that are supportive of CSEs and organizations hosting CSEs. Given the largely atheoretical nature of episodic and CSE volunteering research (Dunn et al, 2015;Hyde et al, 2014), this study draws from two theoretical frameworks validated in volunteering research outside of the CSE context, which may be of relevance to address the gaps identified. First, the volunteer process model (Snyder & Omoto, 2008) proposes key volunteering constructs and links these constructs in three sequential phases: antecedents to volunteering (e.g.…”
Section: The Current Studymentioning
confidence: 99%
“…Thus, volunteering is a specific type of a helping behaviour that has clear boundaries. Furthermore, for the purposes of this review, volunteering is conceptualised as a proactive activity that entails some commitment of time and effort, rather than reactive such as spontaneous volunteering, reviewed elsewhere (Dunn, Chambers, & Hyde, ; Whittaker et al, ). In the 2016 census, 3.62 million of Australians (19% of the population aged 15 years and over) indicated that they were engaged in voluntary work through an organisation or group .…”
Section: Introductionmentioning
confidence: 99%